Tagged a case study on the online campaigning behavior of Barangay Catalunan Grande's Youth Candidates through social networking sites during the Sangguniang Kabataan Elections 2010 - Gaane, Fatima Marie E.
Nowadays, Social Networking Sites are used as a distribution platform to disseminate information, especially among the youth. This research explored on the online campaigning activities of five (5) youth candidates of Barangay Catalunan Grande on the Social Networking Site Facebook before and during the Sangguniang Kabataan Elections conducted last November 2010. As feedback on the youth candidate's online campaign, twenty(20) youth voters were also surveyed about their online activities, regardless if they campaigned online or not. The online behavior of the youth candidates was affected because of the SK elections 2010. Their online activities during the SK elections was utilized since Facebook was the fastest and easiest way for them to campaign and disseminate the information they want to convey to the voters. They influenced the youth voters to vote for them using the Social Networking Site Facebook and it affected the decision-making of the voters
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Media arts